The Influence of Social Media Marketing on Purchase Intention with Customer Relationship Management and Brand Equity as Mediating Variables - Irba’ Muhlas Sambodo (PT SOLUSI EDUKASI BERDIKARI, 2025)
The growth of social media has change method individual interact and influence behavior consumers , including in context digital marketing . Research This aim For analyze influence social media marketing to interest buy with mediation management connection customers and equity brand . Research This use approach quantitative with object undergraduate students from college Islamic higher education institutions in Yogyakarta, namely the Islamic University of Indonesia, Yogyakarta State Islamic University, Muhammadiyah University of Yogyakarta, and Ahmad Dahlan University. Data obtained through online questionnaire and analyzed use multiple linear regression with variables mediation . Research results show that social media marketing influential positive and significant to interest buy . In addition , management connection customers and equity brand proven mediate connection said , shows that effectiveness digital marketing does not only depends on promotion , but also on effort build trust and image strong brand .​